Robust Failure Compensation for a Morphing Aircraft Model Using a Probabilistic Approach - Ataei-Esfahani, Armin; Wang, Qian (IEEE transactions on control systems technology, 2007)
We present a probabilistic robust control design for a morphing aircraft model subject to uncertain actuator failure. The morphing aircraft model has multiple distributed arrays of shape-change devices that are used to generate moments for stabilization and low-rate maneuvering, augmenting conventional control surfaces. Each actuator operates at either on or off state; failure of each actuator could cause uncertainty in the applied control input. We characterize the morphing aircraft's actuation failure in a probabilistic way. In particular, each shape-change device within an actuator array is assumed to have certain probability to fail while devices from different arrays may have different failure probabilities. Consequently, we model the uncertain actuator failure as a random parametric uncertainty in the input matrix of the morphing aircraft model. A probabilistic robust explicit-model-following controller is then designed to stabilize the closed-loop system and to satisfy tracking performance subject to uncertain actuator failure. Simulation results are presented and evaluated for the application of this probabilistic robust failure compensation design to lateral dynamics of an Innovative Control Effector morphing aircraft model